Peripheral Nervous System Reconstruction Reroutes Cortical Motor Output—Brain Reorganization Uncovered by Effective Connectivity - Ahmad Amini; Ahmad Amini; Ahmad Amini; Florian Ph.S. Fischmeister; Florian Ph.S. Fischmeister; Florian Ph.S. Fischmeister; Eva Matt; Eva Matt; Robert Schmidhammer; Frank Rattay; Roland Beisteiner; Roland Beisteiner (Frontiers in Neurology, 2018)
Cortical reorganization in response to peripheral nervous system damage is only poorly understood. In patients with complete brachial plexus avulsion and subsequent reconnection of the end of the musculocutaneous nerve to the side of a phrenic nerve, reorganization leads to a doubled arm representation in the primary motor cortex. Despite, homuncular organization being one of the most fundamental principles of the human brain, movements of the affected arm now activate 2 loci: the completely denervated arm representation and the diaphragm representation. Here, we investigate the details behind this peripherally triggered reorganization, which happens in healthy brains. fMRI effective connectivity changes within the motor network were compared between a group of patients and age matched healthy controls at 7 Tesla (6 patients and 12 healthy controls). Results show the establishment of a driving input of the denervated arm area to the diaphragm area which is now responsible for arm movements. The findings extend current knowledge about neuroplasticity in primary motor cortex: a denervated motor area may drive an auxilliary area to reroute its motor output.